Public Room Door Locking System Using Wireless Technology and Internet of Things - Mahmud Mustapa; Irwan; Ummiati Rahmah; Akbar Iskandar; Ahmed J. Obaid (Ceddi Journal of Information System and Technology (JST), 2024)
Enhancing the efficiency and security of public spaces has become increasingly important, leading to the development of an automatic door lock system utilizing wireless technology and the Internet of Things (IoT). This study aims to design and implement a smart door lock system that provides automated control and improves convenience in managing public room access. The research methodology involves programming the ESP32 microcontroller, integrating IoT applications, and conducting various testing methods. These include manual control through physical switches, automated control via the Sinric Pro platform, and Wi-Fi hotspot-based control using the ESP32 module. Comprehensive hardware and software testing was carried out to ensure system reliability and functionality. The results indicate that the proposed system enables seamless control of public room doors through multiple methods, including an Android-based application and Wi-Fi connectivity. By leveraging IoT technology, the system offers a user-friendly, efficient, and secure solution for managing public space access, addressing modern requirements for convenience and safety.